2013
DOI: 10.1097/rhu.0b013e31827cd578
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hand or Knee Osteoarthritis With Diabetes Mellitus in a Population of Hispanics From Puerto Rico

Abstract: Background Although a higher prevalence of osteoarthritis (OA) has been reported among diabetes mellitus (DM) patients, inconsistencies and limitations of observational studies have precluded a conclusive association. Objective To evaluate the association of hand or knee OA with DM in a population of Hispanics from Puerto Rico. Methods A cross-sectional study was performed in 202 subjects (100 adult DM patients as per the National Diabetes Data Group Classification, and 102 non-diabetic subjects). OA of ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 33 publications
3
83
3
2
Order By: Relevance
“…5,52 Results of a 20-year longitudinal cohort study of 927 individuals suggest that T2DM predicts both joint failure and hip and knee arthroplasty surgery, independently of age, sex, and BMI. 5 This study used both clinical measures (Knee Injury and Osteoarthritis Outcome Score, Western Ontario and McMaster Universities Osteoarthritis Index) and advanced imaging techniques (ultrasound) to assess severity of OA.…”
Section: Association Between Oa and T2dmmentioning
confidence: 99%
“…5,52 Results of a 20-year longitudinal cohort study of 927 individuals suggest that T2DM predicts both joint failure and hip and knee arthroplasty surgery, independently of age, sex, and BMI. 5 This study used both clinical measures (Knee Injury and Osteoarthritis Outcome Score, Western Ontario and McMaster Universities Osteoarthritis Index) and advanced imaging techniques (ultrasound) to assess severity of OA.…”
Section: Association Between Oa and T2dmmentioning
confidence: 99%
“…6,12 We excluded uncontrolled diabetes from our study but patients with controlled glycemic status without insulin for at least one year were evaluated for hand OA and significant association were found between DM and Hand OA. The effect of obesity is apparent in both sexes and is mainly associated with an excess of OA in the weight-bearing joints suggesting a mechanical effect, but in males obesity is also associated with an excess of OA of the DIP joints and the general pattern of OA in obese males approximates to that seen in the total females.…”
Section: Discussionmentioning
confidence: 99%
“…5 Diabetes Mellitus seems to be a risk factor for both hand and knee OA. 6 Familial aggregation of Heberden's nodes was described as early as the 1940s and has since been confirmed for hand osteoarthritis by several studies. 7 Plain radiographs are the method of choice to diagnose hand OA.…”
Section: Introductionmentioning
confidence: 95%
“…And DM, as one important part of metabolic syndromes, is attracting the attention of the function in OA development [5]. In 2003, Mariely and the colleagues compared the data of 100 DM and 102 non-DM patients from Puerto Rico, via the analysis of multivariate regression curve, they showed that 49% of DM patients accompanied with DM, and only 26.5% of non-DM patients showed no OA, suggesting that DM patients had high risk of OA [6]. Then, Georg and the colleagues, by the nearly 20 years' follow-up of 927 participator, showed for the first time that DM was an independent risk factor of OA, with the exclusion of sex, age, BMI and other risk factors [7].…”
Section: Discussionmentioning
confidence: 99%